2004
DOI: 10.1158/1078-0432.ccr-04-0593
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of ERM Gene Expression in Human Primary Breast Cancers

Abstract: We measured the expression of ERM gene, a nuclear transcription factor belonging to the ets family, in a series of 364 unselected primary breast cancers from patients who underwent locoregional surgery in the Centre Oscar Lambret between May 1989 and December 1991. The expression of ERM was quantified with a real-time one-step reverse transcription-PCR assay based on the 5-nuclease activity of the TaqDNA polymerase and with an Abi Prism 7700 Sequence Detector System (Applied Biosystems, Courtaboeuf, France). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 35 publications
4
29
0
1
Order By: Relevance
“…Recent data confirmed the role of Pea3 in breast cancer tumorigenesis and suggest that Pea3 is a marker of tumor aggressiveness rather than a prognostic factor (26). Moreover, we have shown that Erm expression is an adverse prognostic factor for overall survival in breast cancer patients (27).…”
supporting
confidence: 71%
“…Recent data confirmed the role of Pea3 in breast cancer tumorigenesis and suggest that Pea3 is a marker of tumor aggressiveness rather than a prognostic factor (26). Moreover, we have shown that Erm expression is an adverse prognostic factor for overall survival in breast cancer patients (27).…”
supporting
confidence: 71%
“…Correlation between the expression of the tyrosine kinase receptor Her2 and Pea3 has also been shown, since this latter is expressed in the majority of tumors expressing Her2 (Benz et al, 1997;Fleming et al, 2004). Expression of another PEA3 group member, Erm, is detectable in more than 80% of human breast cancers, thus also demonstrating a role of this transcription factor in breast cancer and, more particularly, as an independent adverse prognosis factor for overall survival (Chotteau-Lelievre et al, 2004). In experimental mammary models, it has been demonstrated that ectopic overexpression of Pea3 in non-metastatic human breast-cancer cells increases their invasiveness and their metastasis potential in nude mice (Kaya et al, 1996).…”
Section: Introductionmentioning
confidence: 89%
“…Cdx2 and GCC mRNA and protein expression in tumors and matched normal mucosal specimens were compared using the Wilcoxon signed-rank test (27). Correlation of Cdx2 with GCC expression was quantified by the Spearman correlation coefficient, a nonparametric estimate (28). Cdx2 transcriptional activity in tumors and matched normal mucosal specimens were compared using the Student's t test.…”
Section: Methodsmentioning
confidence: 99%